2012
DOI: 10.1097/bcr.0b013e318234966c
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Nosocomial Infection and Mortality in Burn Patients

Abstract: To evaluate the risk factors for nosocomial infection (NI) and mortality in a university hospital, 10-year data of burn patients were assessed retrospectively. The study was conducted at Erciyes University's Burn Center during 2000 and 2009. The records of 1190 patients were obtained. Overall, 131 (11%) patients had 206 NIs with an incidence density of 14.7 infections/1000 patient days. Burn wound infection (n = 109, 53%) was the most common NI. High (%TBSA burned) and late excision were found to be the most s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
1
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 15 publications
3
61
1
4
Order By: Relevance
“…A. baumannii was the most frequently detected, followed by P. aeruginosa. Among the detected G -rod bacteria from burn patients, A. baumannii exhibited an annually increasing trend that showed a higher detection rate compared with previous reports in literature (Xu et al, 2001(Xu et al, , 2002Essayagh et al, 2011;Alp et al, 2012). A. baumannii is a G -rod bacterium that is not fermented by carbohydrates, and is widely distributed in nature, hospital environments, and human skin.…”
Section: Discussionmentioning
confidence: 41%
“…A. baumannii was the most frequently detected, followed by P. aeruginosa. Among the detected G -rod bacteria from burn patients, A. baumannii exhibited an annually increasing trend that showed a higher detection rate compared with previous reports in literature (Xu et al, 2001(Xu et al, , 2002Essayagh et al, 2011;Alp et al, 2012). A. baumannii is a G -rod bacterium that is not fermented by carbohydrates, and is widely distributed in nature, hospital environments, and human skin.…”
Section: Discussionmentioning
confidence: 41%
“…Moreover, advanced age, underlying diseases, and higher TBSA percentage were the most significant risk factors for mortality in the study. [11] Zarei et al have found that non-work-related burns, burnt TBSA, and body surface area affected by second-or third-degree burns are independent predictors of mortality. [12] Although variables like age, type of injuries, TBSA percentage, co-morbidity, leukocyte, and serum albumin parameters may have affected mortality, only age over 65, TBSA percentage and serum albumin levels were found to be independent risk factors for mortality.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in agreement with the most of previous studies. 61,89,90 The highest level of death caused by infection is probably due to the lack of early wound swab and blood culture for bacteria and sensitivity of organism which is leading to septicemia and then death. Furthermore, a study by Ramakrishnan, M., et al showed that early management and empirical antibiotic regimes decrease wound sepsis resulting to the increase of survival.…”
Section: Mortalitymentioning
confidence: 99%